Problem Loans in the Caribbean : Determinants, Impact and Strategies for Resolution - Beaton, Kimberly (IMF Working Papers; Working Paper ;, 2017)
The high level of nonperforming loans (NPLs) in the Caribbean has been, in large part, a legacy of the global financial crisis, but their persistence owes much to the weak economic recovery in the region, as well as to structural obstacles to their resolution. A comprehensive strategy is needed to address these impediments to sever the adverse feedback loops between weak economic activity and weak asset quality. This paper finds that NPLs are a drag on Caribbean growth and macro-financial links are strong: a deterioration in asset quality hinders bank lending and dampens economic activity, undermining, in turn, efforts to resolve problem loans. A multifaceted approach is needed, involving a combination of macro- economic policies to support growth and employment; strong supervisory frameworks to ensure macro-financial stability and create incentives for resolution; efforts to address informational gaps and deficiencies in insolvency and debt-enforcement frameworks; and development of markets for distressed loans. The institutional capacity constraints require coordination of reforms within the region and support from international organizations through capacity-building.